A népesség iskolázottságának előrejelzése 2020-ig: Iskolázási mikroszimulációs modell (ISMIK) - Zoltán Hermann; Júlia Varga (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– The paper presents a detailed description of the ISMIK model which was developed as a part of "Priority project TÁMOP - 2.3.2-09/1 Establishing labour market forecasts and foreseeing structural changes". The ISMIK model is a dynamic microsimulation model to project individuals' educational participation and qualification. The microsimulation model simulates education events at the individual level. The model projects educational participation and attainment of the population over a period of 20 years (2001-2020) by age, gender, region in 6 qualification categories using a 50 per cent sample of the Hungarian Census of 2001 as the initial model population. We present the results of the base scenario when all parameters (transition probabilities) are assumed to be timeinvariant, that is, this scenario projects education level of the population on the condition that everything continues as in the early 2000s. In addition to the base scenario we present the results of alternative scenarios. The first one investigates what would have been educational attainment of the population had Roma and Non-roma students had the same opportunities in their schooling career. The further scenarios measure the effects of educational policy changes: reducing the duration of compulsory schooling; increasing the share of students in secondary vocational training schools; and reducing the number of state-funded places in higher education.
Keywords: C63; J11; J21; I20; 330; microsimulation; population; educational attainment; education policy; Bildungsniveau; Bildungspolitik; Mikrosimulation; Szenariotechnik; Ungarn